The Effect of Intensive Medical Rehabilitation on the Functional Capacity of TNI Soldiers with Chronic Phase of Lower Extremity Injuries - Rifqi Averrouza (Perkumpulan Kedokteran Militer, 2024)
Rehabilitation plays a crucial role in the recovery of patients, improving their quality of life and reducing the risk of complications by restoring a person's functional capacity after experiencing an injury. Chronic musculoskeletal injuries that are not handled optimally have the potential to cause disability for soldiers, making it impossible for soldiers to return to duty according to their main duties. Lower extremity injury is related to the potential reduction in a person's functional capacity, related to their functions, namely mobility, fitness, strength and agility. Active military soldiers with chronic lower extremity injuries underwent an intensive-structured medical rehabilitation program 3 times a week for 8 weeks. At the end of the rehabilitation program, statistically significant differences were found in the increase in cardiorespiratory fitness capacity and agility compared to pre-intervention. Even in chronic conditions, intensive medical and structural rehabilitation programs in cases of lower limb injuries can significantly increase functional capacity in assessing cardiorespiratory fitness and agility in accordance with TNI soldier fitness standards.